2013
DOI: 10.1080/03601234.2013.742412
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent sorption behavior of dinotefuran, imidacloprid and thiamethoxam

Abstract: Dinetofuran (DNT), imidacloprid (IMD) and thiamethoxam (THM) are among the neonicotinoid insecticides widely used for managing insect pests of agricultural and veterinary importance. Environmental occurrence of neonicotinoid in post-application scenario poses unknown issues to human health and ecology. A sorption kinetic study provides much needed information on physico-chemical interaction of neonicotinoid with soil material. In this research study, time-dependent sorption behavior of DNT, IMD and THM in vine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 15 publications
4
26
0
3
Order By: Relevance
“…Liquid or solids in the used fly media may have removed imidacloprid in or on the parasitoids to levels that did not reduce fly killing and parasitoid reproduction. Imidacloprid is highly soluble in water (Kurwadkar et al 2013) and adsorbs to organic matter (Cox et al 1998). In contrast, when imidacloprid remains on a female, it may be absorbed through non-sclerotized parts of the insect's cuticle, as seen in fleas (Mehlhorn et al 1999); or females may also consume it as they groom because grooming frequently involves pulling the antennae and legs through the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid or solids in the used fly media may have removed imidacloprid in or on the parasitoids to levels that did not reduce fly killing and parasitoid reproduction. Imidacloprid is highly soluble in water (Kurwadkar et al 2013) and adsorbs to organic matter (Cox et al 1998). In contrast, when imidacloprid remains on a female, it may be absorbed through non-sclerotized parts of the insect's cuticle, as seen in fleas (Mehlhorn et al 1999); or females may also consume it as they groom because grooming frequently involves pulling the antennae and legs through the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…The TM-release kinetics performance was tested according to a previous test method reported in the literature. 21,22 Before measurement, the TM adsorbed the PCSE and LAMI-modied PCSEs samples were dried in a vacuum oven at 40 C for 5 h. Then, the above samples were weighed and placed in a dialysis bag with 20.0 mL water. The dialysis bag was put in a 250 mL conical ask lled with 100.0 mL water.…”
Section: Thiamethoxam Release Kinetics From the Pcse And Lami-modiedmentioning
confidence: 99%
“…In our study, the phenomena could be observed in our bare land control, showing a high amount of dinotefuran retained in the surface soil right after application, and in the imidacloprid retained almost throughout the experiment. The different distribution of the two neonicotinoids in the bare land control could be explained by the different physical properties of the two pesticides, such as Koc and water solubility [14,15]. Dinotefuran has better water solubility than imidacloprid, which may explain the higher plant absorption and higher groundwater contamination potential with C. brownei planting.…”
Section: Discussionmentioning
confidence: 99%